Konsep Dasar Pembinaan Kesadaran Beragama Dalam Dunia Pendidikan Anak - Khanif Maksum (Universitas Alma Ata, 2012)
Religious awarness in a person is an important factor in determining peace and happiness of human life. Because it will guide him endure his/her life solidly and strongly foundation in the world. In early childhood, religion awarness should be emphasized properly and sustainably, in order to be internalized in next thier life. Therefore, in young generation education, moral and religious life required consistent and serious attention. Improving of religious life for children, can be a positive influence on the life of children, both in culture, social and religious segments. Children can keep themselves from a moral action among the students and young generation and to avoid from current of a negative culture which is disseminate through multiple media, eg. news paper, readings, pictures, broadcasts and performances. Keywords: Religious awareness, life of children